Perspectives on the Poudre River World Café: gathering collective wisdom to explore stakeholder visions of the Poudre River - Center for Collaborative Conservation, author (Colorado State University. Libraries, 2014)
For this world café, we anticipate in-depth conversations that lead to feasible and collaborative ideas about sustaining the health and productivity of the Poudre River. This world cafe will be the culmination of the CCC Fall Seminar and Discussion Series about the Poudre River. We aim to integrate agricultural, ecological, recreational, legal, and local citizen perspectives concerning the Poudre River. Interest groups and participants may include water rights lawyers, ditch companies, farmers and ranchers, researchers, local government, NGOs, students, and Larimer and Weld County residents. World Cafe Objectives • To integrate diverse stakeholder visions and perspectives on sustaining the ecological health of the Poudre River while recognizing its role as a working river for agriculture and cities • To discuss ways for bridging and efficiently communicating about multiple stakeholder visions concerning the Poudre River.
A World Café dialogue: perspectives on the Poudre
This document outlines a collection of participant insights shared during the World Café dialogue at the New Belgium Brewery in Fort Collins, Colorado on December 9, 2014. This event was the culmination of a series of eight seminars on the Poudre River hosted by the Center for Collaborative Conservation (CCC). This event was also co-hosted and sponsored by the Poudre Runs Through It Study/Action Work Group.
Unfamiliar with what a World Café is? It is a type of organizational workshop, which aims to provide an open and creative conversation on a topic of mutual interest to surface their collective knowledge, share ideas and insights, and gain a deeper understanding of the subject and the issues involved.
This is a special seminar where ideas on the Poudre River were shared.